An Integrative Serum Pharmacology-Based Approach to Study the Anti-Tumor Activity of B. paniculatum Aqueous Bulb Extract on the Human Hepatocellular Carcinoma Cell Line BEL-7404 - Feng, Xuesong; Ma, Guangyuan; Shi, Hailong; Wang, Yuewen; Chao, Xu (Frontiers in Pharmacology, 2020)
The herb Bolbostemma paniculatum, also known as Tu-Bei-Mu (TBM), has shown curative effects to treat several types of cancer as an adjunctive therapy. Thereby we intend to find its effect on the human hepatocellular carcinoma (HCC) and to understand the pharmacological mechanism behind. In this study, an integrative serum pharmacology-based approach linking serum pharmacology and bioinformatics prediction was employed. Firstly, we use the serum from rats introgastric administered by TBM aqueous bulb extract to culture the HCC cell line BEL-7404 and detect its anti-tumor effects. Secondly, the TBM putative targets were predicted using ETCM database and known therapeutic targets of NPC were collected from OMIM database. Then, a TBM-HCC putative targets network and was constructed using DAVID and STRING database. Thirdly, key gene targets were obtained based on topological analysis and pathway enrichment analysis. And the expression of certain key targets were validated by Western blotting. As a result, 36 TBM’s targets and 26 known therapeutic targets of HCC was identified. These key targets were found to be frequently involved in 13 KEGG pathways and 4 biological processes. The expression of four representative key targets: TP53, CASP3, BCL2 and BAX further supports the suppression of TBM on HCC. In general, our study shows the curative effects of TBM against HCC. By using this integrative approach, we may find novel potential therapeutic targets to treat HCC using TBM. And it could also help us understand the mechanism of HCC treatments in response to TBM.